Ipse Enim est Pax Nostra: Ephesians 2:14 in the Preaching of St. Augustine - Yates, Jonathan P. (Editorial Uniagustiniana, 2019)
This chapter elucidates Augustine's uses of Paul's phrase "ipse enim est pax nostra" (Eph. 2:14a) within his extant preaching. Although primarily exegetical and theological, the implications of this exegesis and theology for spirituality and ecclesiology are also discussed. Contemporary biblical scholars often limit Eph. 2:14's claims to reconciliation between Jews and Gentiles, and the way(s) that this reconciliation serves as a basis for living out the bond between God and his people and as an inspiration for peace in this world. However, for Augustine, Eph. 2:14 teaches even more about living the Christian life and about reconciling human beings, whether they are inside or outside the visible church. Augustine employed Eph. 2:14 more than sixty times in various contexts. Eph. 2:14 appears in sermons for both Christmas and for Epiphany, in sermons directly or indirectly addressing Jews, Pelagians, and Donatists, and in sermons intended to educate or encourage particular congregations. The true import of Ephesians 2:14a for Augustine is most clearly seen, however, in his overtly exegetical sermons. In these, Augustine invokes Eph. 2:14 to emphasize the necessity of faith in Christ for experiencing peace either in this age or in the age that is to come, that Christ is the only genuine pacificus, and that Israel's "true" identity is only found among those who are united with the trans-temporal church. The sermons for Epiphany, which are by definition anti-Donatist, often plead for reconciliation, even as they cast doubt upon the genuineness of Donatist claims to possess faith in Christ.